Clinical and epidemiological characterization of patients con HIV/Aids assisted in an urgencies and emergencies service - Reinier Besse Díaz; Lázaro Ibrahim Romero García; Emilio Cobo Montero; Laidelbis Minier Pouyou; Evelyn Esther Suárez (Centro Provincial de Información de Ciencias Médicas, 2018)
A descriptive, cross-sectional and retrospective study of 64 Aids patients assisted at the Urgencies and Emergencies Service of "Dr. Juan Bruno Zayas Alfonso" Teaching General Hospital was carried out in Santiago de Cuba from January, 2015 to the same month in 2017, with the objective of characterizing them according to clinical and epidemiological variables of interest for the investigation. Male sex, the age group 15-30, acute gastritis and the loss of consciousness as the most frequent causes of medical care (31.2 and 23.4 %, respectively), as well as the septic shock as main complication prevailed in the series . It is concluded that the Aids generally affects the youngest and the severe complications are quite frequent, although the magnitude of the deaths is low and the hospital stay is variable.